A long wavelength colourimetric chemosensor for fluoride. Issue 9 (2nd September 2018) - Marchetti, Luke A.; Mao, Nan; Krämer, Tobias; Kitchen, Jonathan A.; Elmes, Robert B. P.
Abstract: A family of chemosensors based on the squaramidoquinoxaline moiety (cyclobuta[b]quinoxaline-1, 2(3H, 8H)-dione) (1–3 ) have been assembled by a simple room temperature one step synthesis. X-ray crystallographic analysis of2 demonstrated both strong hydrogen bond donor ability and tendency to π stack in the solid state. Moreover, Compound2, with its strongly electron withdrawing nitro-substituent, showed an obvious F − selective colour change (when measured against other halides) clearly visible to the naked eye from pink to green in DMSO solution. Further addition of F − led to a second colour change from green to yellow. Using TD-DFT, UV/Vis and NMR analysis we conclude that the observed colour changes are likely to be due to a two-step process involving two NH deprotonation steps. Colour changes of1 and3 were not as apparent in the presence of F − owing to the reduced acidity of the NH functionality of the squaramidoquinoxaline. The results of this study again demonstrate the use of squaramide derivatives as valuable building blocks in the field of anion recognition and demonstrate that the electron withdrawing aryl substituent is directly related to the sensing ability/acidity of the squaramide protons and can be used to tune their anion recognition behavior. Abstract :